Green Marketing as a strategy for sustainable purchasing behavior in Mexico - Valenzuela Nájera, Ashley Itzel (Memorias del Concurso Lasallista de Investigación, Desarrollo e innovación, 2019)
Nowadays, environmental deterioration is considered as a public problem. The need to stop the current trends that contribute to its destruction, like intense consumption and the effect of business activities, has led to the application of Green Marketing strategies. The aim of this article is to analyze, in a sample of 190 Marketing students, the influence these strategies have on young Mexican consumers when trying to change their consumption behavior and encourage them to purchase green products. Based on the Chi Square Test used to examine the questionnaire we applied; the results indicate that there was a significant difference between gender when considering an ecological production before buying a product. A lack of knowledge of Green Marketing strategies was also revealed, obtaining differences between salary, work and semester. According to our analysis, companies in Mexico should improve three key factors for their strategies to have a greater impact. More attention should be given to young male consumers, more innovative ways of promotion and an ecological production process must be developed.